Handbook of sustainability for the food sciences - Morawicki, Rube´n O. (Wiley-Blackwell, 2012)
Many books on sustainability that have emerged in the last decade have been written for agricultural systems, communities, and business in general. This handbook presents the concept of sustainability as adapted to the food industry